2016
DOI: 10.1093/intimm/dxv113
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial cathelicidin peptide LL-37 inhibits the pyroptosis of macrophages and improves the survival of polybacterial septic mice

Abstract: LL-37 is the only known member of the cathelicidin family of antimicrobial peptides in humans. In addition to its broad spectrum of antimicrobial activities, LL-37 can modulate various inflammatory reactions. We previously revealed that LL-37 suppresses the LPS/ATP-induced pyroptosis of macrophages in vitro by both neutralizing the action of LPS and inhibiting the response of P2X7 (a nucleotide receptor) to ATP. Thus, in this study, we further evaluated the effect of LL-37 on pyroptosis in vivo using a cecal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 40 publications
3
75
0
1
Order By: Relevance
“…Interestingly, a previous study reported that Camp KO mice exhibit the increased survival and upregulation of key inflammatory response genes following cecal ligation and puncture (CLP), an established experimental model of polymicrobial sepsis . However, another study showed that LL‐37 improves the survival of CLP septic mice possibly by suppressing the pyroptosis of macrophages, inflammatory cytokine production, and bacterial growth . These studies imply that cathelicidin has a complex role in the CLP septic model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a previous study reported that Camp KO mice exhibit the increased survival and upregulation of key inflammatory response genes following cecal ligation and puncture (CLP), an established experimental model of polymicrobial sepsis . However, another study showed that LL‐37 improves the survival of CLP septic mice possibly by suppressing the pyroptosis of macrophages, inflammatory cytokine production, and bacterial growth . These studies imply that cathelicidin has a complex role in the CLP septic model.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the therapeutic application of exogenous LL‐37 administration in sepsis has been widely investigated. These studies have shown that LL‐37 treatment protects mice against sepsis by suppressing apoptosis of endothelial cells, preventing intestinal barrier dysfunction, and inhibiting the pyroptosis of macrophages, inflammatory cytokine production, and bacterial growth . However, the influence of cathelicidin on septic cardiac defect is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Ayres et al found that inflammasome activation in a mouse model of Escherichia coli resulted in IL-1β–driven lethal immunopathology, which could not be tolerated by the host34. Inhibiting inflammasome signaling and pyroptosis by caspase-1 specific inhibitors or caspase-1 and NLRC4 knockout also significantly alleviated tissue damage, decreased bacterial burden, and increased the survival rate of infected mice32333435.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the administration of LL-37 significantly suppressed the CLP-induced caspase-1 activation and pyroptosis of peritoneal macrophages ( Figure-4B and C). Moreover, LL-37 modulated the levels of inflammatory cytokines (IL-1β, IL-6 and TNF-α) both in the peritoneal fluids and sera and suppressed the activation of peritoneal macrophages (as evaluated by the increase in the intracellular levels of IL-1β, IL-6 and TNF-α) 31) . Furthermore, LL-37 reduced the bacterial burdens both in peritoneal fluids and blood samples 31) .…”
Section: Inhibition Of the Macrophage Pyroptosis And Improvement Of Tmentioning
confidence: 96%
“…Moreover, LL-37 modulated the levels of inflammatory cytokines (IL-1β, IL-6 and TNF-α) both in the peritoneal fluids and sera and suppressed the activation of peritoneal macrophages (as evaluated by the increase in the intracellular levels of IL-1β, IL-6 and TNF-α) 31) . Furthermore, LL-37 reduced the bacterial burdens both in peritoneal fluids and blood samples 31) . Thus, our present study suggests that LL-37 improves the survival of CLP septic mice by possibly suppressing the pyroptosis of macrophages, and inflammatory cytokine production by activated macrophages as well as bacterial growth (Figure-5, right panel).…”
Section: Inhibition Of the Macrophage Pyroptosis And Improvement Of Tmentioning
confidence: 96%